A Comparison of Materials for Dry Surface Cleaning Soot-Coated Papers of Varying Roughness: Assessing Efficacy, Physical Surface Changes, and Residue. Issue 2 (3rd April 2023) - Duncan, Teresa T.; Vicenzi, Edward P.; Lam, Thomas; Brogdon-Grantham, Shannon A.
ABSTRACT: To provide detailed information to aid conservators faced with soot removal, a survey comparing the removal of lamp black pigment, serving as a model soot, from three sample papers of differing roughness is presented. The efficacy of ten different dry surface cleaning materials—including sponges, firm and kneaded erasers, eraser crumbs, a cleaning putty, a solvent-free polydimethylsiloxane elastomer, and a dry swab—have been assessed using a handheld color spectrophotometer and image analysis of photomicrographs. Inspection of the cleaned substrates with a portable optical microscope revealed detailed information into how physical properties of cleaning materials influence the location of residual soot on the surface. 3D digital light microscopy and Fourier-transform infrared spectroscopy were used to assess physical changes to the paper surface and to identify potential residues from the materials after cleaning, respectively. The results of this model study were compared with spot cleaning tests performed on a fire-damaged paper book cover. Limited access to laboratory spaces during Covid-19 lockdown motivated this research to focus on affordable ways to perform hands-on technical research outside of the laboratory, details of which are noted throughout this paper.